Characterization of Yellow Pigmented Bacteria Associated with Gracilaria sp. - Lunggani, Arina Tri; Purwantisari, Susianna; Jannah, Siti Nur (Advance Sustainable Science, Engineering and Technology, 2020)
Research on the kinship analysis of endophytic bacterial  isolated from Gracillaria sp has been carried out. The presence of bacteria associated with Gracilaria sp. has enabled the use of these bacteria as a source of new bioactive compounds, such as biopigments. The research aims to isolated bacteria from Gracilaria sp., screened their symbiont bacteria that could potentially produce pigments. Sampling Gracilaria sp. conducted in the waters of the Island of  Karimunjawa, Jepara. Furthermore, bacterial isolation was carried out, screening for pigment-producing bacteria and 16S rRNA sequence analysis. Research result showed that the symbiont bacteria isolate TK 373 produced consistent pigments after several regenerations, in several types of growth media incubated at room temperature. The results of 16S rDNA identification showed that the TK 373 isolate had the closest relationship with  Pseudoalteromonas sp. with  98.72 % homology.